Animal assisted therapy for incarcerated youth: A randomized controlled trial. Issue 2 (3rd April 2018) - Seivert, Nicholas P.; Cano, Annmarie; Casey, Rita J.; Johnson, Amy; May, Dana K.
ABSTRACT: Teacher's Pet, an animal assisted therapy (AAT) was assessed in a randomized controlled trial with incarcerated youth from two Midwestern United States detention facilities. The AAT was expected to increase empathy and reduce behavior problems. Participants trained dogs for one hour, twice weekly for ten weeks. A control group walked but did not train dogs for the same duration. Both groups attended one hour, twice weekly animal didactics. Of 138 participants, 117 provided complete data, and 21 had some missing data imputed. Contrary to expectation, both groups increased slightly in self-reported empathy, and staff and youth rated internalizing problems. The time youth spent with dogs plus animal didactics may have increased empathy. Increased internalizing problems could be attributed to youth gaining greater emotional awareness. Alternately, this brief intervention may not have any immediate effects, given the small changes observed. Additional follow-up of these youth and other comparison groups are needed.